Pengaruh Kepemilikan Publik, NPM, Pertumbuhan Perusahaan, dan Solvabilitas terhadap Pengungkapan CSR pada Perusahaan Infrastruktur - Deasy Arisandy Aruan; Veronica; Celine Liandy; Debby Christina; Fanny Fanny (Politeknik Ganesha Medan, 2021)
This research’s purposeisto determine the impactof Public Ownership, Net Profit Margin, Company Growth, and Solvency on Corporate Social Responsibility Disclosures. Thisresearchused a quantitative method and Collection Technique is a documentation technique. The population in this research is includes 82 Infrastructure Companies listed on the Indonesia Stock Exchange for the 2015-2019 period. With a sample of 25 Infrastructure companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique in this research is porpusive sampling. The data used in this research is secondary data taken from www.idx.co.id. This research uses multiple linear regression analysis model. The results show that Public Ownership, Net Profit Margin and Company Growth partially had no significant impact on Corporate Social Responsibility Disclosure. Meanwhile, Solvency has a significant positive impact on Corporate Social Responsibility Disclosure. According to simulation, Public Ownership, NPM, Company Growth, and Solvency have no significant impact on Corporate Social Responsibility Disclosure. Testing the analysis of the coefficient of determination shows the results of the adjusted R square value in the coefficient of determination test is 2.6%, where the remaining 97.4% is influenced by other variables such as deferred exploration and development costs, media disclosure, Leverage, and others.It Indicates thatindependent variables in this research are not sufficiently influential on CSR disclosure because there are still many other variables that have a major influence on CSR Disclosure.